Problems faced during rehearsals with piano accompanist in music students of Universiti Teknologi Mara (UiTM) / Ken Iwasaki Muhammad Moritoshi - Muhammad Moritoshi, Ken Iwasaki (2014)
The overall aim of this research was to identify the problems faced during rehearsals with piano accompaniment, the factors that caused the problems, and its influences to the actual performance‘ This research assists soloists and accompanists to understand each parts role and to be able to rehearse effectively during rehearsals‘ The methodology applied was using a qualitative method. where questionnaires based on objective questions were given randomly to 40 students, males and females, from degree in performance department in Faculty of Music, Universiti Teknologi Mara (UiTM)‘ All of the data was collected and analyzed within 3 10 5 weeks. Tables are used to Show the findings to clarify the differences. The results of this research have shown that the problems faced during rehearsal are strongly related to the problems that occur during the actual performance The researcher therefore discovered and concluded that proper preparation will lead us to qualified performance